2017
DOI: 10.1002/term.2436
|View full text |Cite
|
Sign up to set email alerts
|

Engineering vascularized flaps using adipose-derived microvascular endothelial cells and mesenchymal stem cells

Abstract: Human adipose-derived microvascular endothelial cells (HAMEC) and mesenchymal stem cells (MSC) have been shown to bear angiogenic and vasculogenic capabilities. We hypothesize that co-culturing HAMEC:MSC on a porous biodegradable scaffold in vitro, later implanted as a graft around femoral blood vessels in a rat, will result in its vascularization by host vessels, creating a functional vascular flap that can effectively treat a range of large full-thickness soft tissue defects.HAMEC were co-cultured with MSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…Bioprinting technology allows to address this vascularization challenge with some innovative approaches. Endothelial cells (ECs) from different sources, such as primary human umbilical vein endothelial cells (HUVECs), primary human dermal microvascular endothelial cells (HDMECs), or stem cell-derived ECs, have therefore been used as cellular building blocks for the fabrication of vascularization precursors in many forms (Alajati et al, 2008;Freiman et al, 2017;Heiss et al, 2015;Jain, Au, Tam, Duda, & Fukumura, 2005;Laschke & Menger, 2017).…”
mentioning
confidence: 99%
“…Bioprinting technology allows to address this vascularization challenge with some innovative approaches. Endothelial cells (ECs) from different sources, such as primary human umbilical vein endothelial cells (HUVECs), primary human dermal microvascular endothelial cells (HDMECs), or stem cell-derived ECs, have therefore been used as cellular building blocks for the fabrication of vascularization precursors in many forms (Alajati et al, 2008;Freiman et al, 2017;Heiss et al, 2015;Jain, Au, Tam, Duda, & Fukumura, 2005;Laschke & Menger, 2017).…”
mentioning
confidence: 99%
“…Therefore, almost all implanted cells must have been degraded to the time point of histological evaluation. Taken together, we assume that the formation of adipose tissue and the neovascularization is more likely attributable to mediators, secreted by seeded ASCs and SVF cells . These agents might, for example, be IGF, VEGF, bFGF, and HGF …”
Section: Discussionmentioning
confidence: 91%
“…Taken together, we assume that the formation of adipose tissue and the neovascularization is more likely attributable to mediators, secreted by seeded ASCs and SVF cells. 19,22,43,44 These agents might, for example, be IGF, VEGF, bFGF, and HGF. 28,45 In a clinical setting, both mechanisms of tissue formation, namely either the mediated migration of host cells to the scaffold or the differentiation of implanted cells, would go hand in hand, as autologous transplantation of SVF cells is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…While much progress has been made in the field of tissue engineering, most studies utilize immunocompromised animal models or administer immunosuppressive therapy to study the integration and survival of human engineered tissues in animals [8][9][10][11][12][13][14]. These works have established that in vitro graft prevascularization by human vascular cells is beneficial for graft integration and neovascularization post-implantation [8][9][10]13,[15][16][17]. It was also shown that culturing human vascular cells on biodegradable and biocompatible poly (l-lactic acid)/poly (lactide-co-glycolic acid) (PLLA/PLGA) scaffolds combined with fibrin gel results in the spontaneous formation of vessel-like structures in vitro, which later anastomose with the host vasculature upon transplantation into immunocompromised animals [9,16,18].…”
Section: Introductionmentioning
confidence: 99%